Filipino Basic Education Teachers’ Awareness of and Attitude towards the Child Protection Policy - L. dela Fuente, Cleofe (Future Science / FSH-PH Publications, 2021)
Schools shall be conducive to children’s education, and that the children’s’ best interest shall be the primary consideration in all policies and actions of educational institutions. This descriptive cross-sectional survey gauged the Filipino public school teachers’ awareness of and attitudes towards the child protection policy (CPP). The study involved 99 basic education teachers in select public elementary and secondary schools in Zambales, Philippines. The basic education teachers are aware of the policy, and they have a favorable attitude toward its implementation. No significant difference has been found in their awareness and attitude towards CPP when grouped according to demographics. The study concludes that as the teachers become aware of the policy, they tend to have a more favorable attitude. The study recommends that the teachers be capacitated through continuing professional development programs to provide special protection to children who are seriously susceptible or threatened by situations that distress their normal growth. Further study may also be conducted to probe other CPP dimensions in basic education to come up with relevant and research-based recommendations towards the policy’s improved implementation in the public schools in the Philippine context.